2018
DOI: 10.1021/acsami.8b12908
|View full text |Cite
|
Sign up to set email alerts
|

Highly Advanced Degradation of Thiamethoxam by Synergistic Chemisorption-Catalysis Strategy Using MIL(Fe)/Fe-SPC Composites with Ultrasonic Irradiation

Abstract: MIL(Fe)/Fe-doped nanospongy porous biocarbon (Fe-SPC) composite was fabricated from MIL-100(Fe) via in situ growth on a unique Fe-doped nanospongy porous biocarbon (Fe-SPC) and was used as Fenton-like catalyst for advanced degradation of thiamethoxam (THIA). Fe was loaded on silkworm excrement and calcined to Fe-SPC with nanospongy and high sp 2 C structure. The in situ growth strategy embedded the Fe-SPC into MIL-100(Fe) crystals and formed conductive heterojunctions with an intensified interface by Fe-bridgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…According to “hard and soft acid base” theory, isopropanol is classified as a hard base with strong affinity towards hard acids. Thus, Zr sites with higher hardness should preferably attract isopropanol [36] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to “hard and soft acid base” theory, isopropanol is classified as a hard base with strong affinity towards hard acids. Thus, Zr sites with higher hardness should preferably attract isopropanol [36] …”
Section: Resultsmentioning
confidence: 99%
“…Thus, Zr sites with higher hardness should preferably attract isopropanol. [36] Herein, according to the different adsorption ability of isopropanol on MOFs, zirconium (Zr) was selected to partially substitute Fe ions in MIL-100(Fe) to obtain the MIL-100(Fe-Zr) complex. Its XPS pattern showed that about 2 % of Zr was successfully replaced Fe on the MIL-100(Fe) surface ( Figure S9) via the ion exchange strategy.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…41,42 It is attributed to a special reconstruction of lamellar structures from mulberry leaf cellulose by silkworms through intestinal absorption. 43,44 After being calcinated with Fe species, SE was transformed into a 3D nano-spongy network packed with nanosheets (Figures S3B and 2B). This new Fe@C composite possesses many porous channels, providing a great diffusion pathway for molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs), which are assembled with metal ions and multidentate organic linkers, have been intensively studied as a new class of porous materials. Due to their unprecedented specific surface area, adjustable chemical composition, and tunable porosity, MOFs have been considered as one of the most promising materials for various applications, such as gas storage and separation, catalysis, sensing, and dehumidification. , …”
Section: Introductionmentioning
confidence: 99%